2010
DOI: 10.1371/journal.pone.0014058
|View full text |Cite
|
Sign up to set email alerts
|

Identification of 20-Hydroxyecdysone Late-Response Genes in the Chitin Biosynthesis Pathway

Abstract: Background20-hydroxyecdysone (20E) and its receptor complex ecdysone receptor (EcR) and ultraspiracle (USP) play a crucial role in controlling development, metamorphosis, reproduction and diapause. The ligand-receptor complex 20E-EcR/USP directly activates a small set of early-response genes and a much larger set of late-response genes. However, ecdysone-responsive genes have not been previously characterized in the context of insect chitin biosynthesis.Principal FindingsHere, we show that injection-based RNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
74
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 97 publications
(77 citation statements)
references
References 49 publications
3
74
0
Order By: Relevance
“…Ecdysteroids induce the so-called early genes and the biosynthesis of regulatory proteins, which in turn activate effector, or late, genes in a secondary response [67]. Among the effector genes are those encoding cuticular proteins and enzymes in the tanning pathway, as verified in the lepidopteran Spodoptera exigua [68]. …”
Section: Discussionmentioning
confidence: 99%
“…Ecdysteroids induce the so-called early genes and the biosynthesis of regulatory proteins, which in turn activate effector, or late, genes in a secondary response [67]. Among the effector genes are those encoding cuticular proteins and enzymes in the tanning pathway, as verified in the lepidopteran Spodoptera exigua [68]. …”
Section: Discussionmentioning
confidence: 99%
“…chitin biosynthesis genes) that participate in molting and metamorphosis (Nakagawa and Henrich, 2009;Yao et al, 2010) (Fig. 1).…”
Section: Discussionmentioning
confidence: 99%
“…PBDEs are comprised of 209 congeners. Among Tata (2002) and Yao et al (2010). and Bengtssonet, 2001;Wollenberger et al, 2005). The water flea Daphnia magna showed significant disruption of its developmental molting process in response to 20 g/L BDE-47 (Davies and Zou, 2012), suggesting that BDE-47-induced developmental retardation may be associated with a disturbed ecdysteroid signaling pathway.…”
Section: Introductionmentioning
confidence: 95%
“…This analysis shows that some mutations result in the arrest of ecdysone-responses during metamorphosis (e.g., larval molting) and tissue remodeling (Hwang et al 2010;Lam & Thummel. 2000;Schubiger et al 1998;Verras et al 1999;Wu et al 2012;Yao et al 2010). In insects, increased 20E levels can induce the expression of genes, which is essential for the synthesis of the new cuticle and the production of ecdysis-triggering hormone receptors preparatory to molting.…”
Section: Discussionmentioning
confidence: 99%
“…This gene is also involved in programmed cell death in the anterior silk gland (Jindra & Riddford 1996;Goncu & Parlak 2009). Besides, EcR genes participate in the chitin biosynthesis pathway, which is the major polysaccharide layer in the trachea, muscle, cuticle and peritrophic matrix (Yao et al 2010). In this study, we found that during the last larval stadium, the mRNA transcript of BdEcR-B1 is regulated in a tissuespecific manner in that relatively high amounts of mRNA are found in the gut and Malpighian tubule, and this indicates that the BdEcR-B1 is expressed in a tissue-specific manner, i.e., that the gut and the Malpighian tubule are the main expressing tissues, and that BdEcR-B1 may be essential in tissue remodeling.…”
Section: Discussionmentioning
confidence: 99%